Cheminements professionnels masculins - Spain, Armelle; Bédard, Lucille; Paiement, Lucie (Canadian Journal of Counselling and Psychotherapy, 2007)
In this article, the authors present part of the results of a study on some men’s professional paths from a relational point of view. Although previous research supports the centrality of the relational dimension in women’s vocational development has been found, it is unclear whether this is the case for men. The authors interviewed 12 men, aged between 24 and 62 and describe their professional paths, trying to understand the dynamic movement of their professional lives as they reconstruct it. Within a context where the world of work is being transformed, the conclusions indicate counselling interventions that may be suitable for men.